Electronic arbitration mechanism in settling e-commerce disputes - BENGUERDI, Amine (Journal of Human Sciences, 2025)
In the face of the judiciary’s inability to keep pace with the electronic revolution and to provide swift means for resolving e-commerce disputes, the need has become urgent to search for more successful ways to resolve disputes and disagreements between contracting parties while simultaneously adhering to the requirements of e-commerce, which are based on speed. As a result of these efforts, electronic arbitration has emerged. Arbitration stands as an exceptional pathway for dispute resolution, stemming from mutual agreement and diverging from conventional litigation methods. Its purpose lies in resolving disputes by reaching a verdict issued by an arbitration panel, which holds comparable validity to a court ruling.